Victim Precipitation Sebagai Pertimbangan Dalam Penjatuhan Pidana (Kajian Perspektif Sistem Peradilan Pidana) - Patrick Corputty; Deassy Jacomina Anthoneta Hehanussa; Julianus Edwin Latupeirissa (Criminal of Law Department, Faculty of Law, Pattimura University, 2021)
Victim precipitation was originally a criminological theory and was later developed into victimology which explains that in victimization (criminal acts), the victim can be a contributing factor in the victimization. The aim is to analyze the model of criminal imposition by considering victim precipitation. This research is a sociolegal research. The results obtained by Victim precipitation as a judge's consideration in imposing a crime are used in several general criminal cases.